2010
DOI: 10.1074/jbc.m110.107649
|View full text |Cite
|
Sign up to set email alerts
|

GIPC1 Interacts with MyoGEF and Promotes MDA-MB-231 Breast Cancer Cell Invasion

Abstract: GIPC1/synectin, a single PDZ domain-containing protein, binds to numerous proteins and is involved in multiple biological processes, including cell migration. We reported previously that MyoGEF, a guanine nucleotide exchange factor, plays a role in regulating breast cancer cell polarization and invasion. Here

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 58 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…To test this possibility, we examined whether exogenous expression of a carboxyl-terminal fragment lacking the carboxyl-terminal PDZ-binding motif (MyoGEF-501-780-⌬SEV) interfered with actin filament formation. We have found previously that MyoGEF polypeptides that lack the carboxyl-terminal three residues (SEV) do not bind to GIPC1 (46). As shown in Fig.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…To test this possibility, we examined whether exogenous expression of a carboxyl-terminal fragment lacking the carboxyl-terminal PDZ-binding motif (MyoGEF-501-780-⌬SEV) interfered with actin filament formation. We have found previously that MyoGEF polypeptides that lack the carboxyl-terminal three residues (SEV) do not bind to GIPC1 (46). As shown in Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Our previous findings have shown that the carboxyl-terminal end of MyoGEF contains a PDZ-binding motif that can interact with the PDZ domain-containing protein GIPC1 (46). Therefore, it is possible that exogenous expression of MyoGEF-501-790, which contains the carboxyl-terminal PDZ-binding motif, could interfere with actin organization by disrupting the GIPC1-MyoGEF interaction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations